Analysis of Listen Before Talk Protocol Implementation in Terrestrial Network Using Multi-Node LoRa Communication - Shafiatullaily Mahmud (Advance Sustainable Science Engineering and Technology, 2023)
Wireless communication today plays a very important role in technological development but often faces challenges in terms of reliability and quality of data transmission; this study implements the Listen Before Talk (LBT) protocol in the terrestrial network environment through Multi-Node LoRa communication to test its effectiveness in avoiding packet loss ending the quality of communication in variations of the land environment. Test results showed that LBT effectively produced zero percentage packet loss at 50 to 500 meters. At the same time, LoRa devices could maintain communication quality even though the Received Signal Strength Indicator (RSSI) value decreased with the distance. The findings provide positive indications of the potential of LBT protocols inning data transmission integrity in terrestrial environments and foster the development of reliable and high-quality wireless communications in complex ground network environments.